Methods of using mobile Internet devices in the formation of the general professional component of bachelor in electromechanics competency in modeling of technical objects - Yevhenii O. Modlo; Serhiy O. Semerikov; Ruslan P. Shajda; Stanislav T. Tolmachev; Oksana M. Markova; Pavlo P. Nechypurenko; Tetiana V. Selivanova (Academy of Cognitive and Natural Sciences, 2020)
The article describes the components of methods of using mobile Internet devices in the formation of the general professional component of bachelor in electromechanics competency in modeling of technical objects: using various methods of representing models; solving professional problems using ICT; competence in electric machines and critical thinking. On the content of learning academic disciplines "Higher mathematics", "Automatic control theory", "Modeling of electromechanical systems", "Electrical machines" features of use are disclosed for Scilab, SageCell, Google Sheets, Xcos on Cloud in the formation of the general professional component of bachelor in electromechanics competency in modeling of technical objects. It is concluded that it is advisable to use the following software for mobile Internet devices: a cloud-based spreadsheets as modeling tools (including neural networks), a visual modeling systems as a means of structural modeling of technical objects; a mobile computer mathematical system used at all stages of modeling; a mobile communication tools for organizing joint modeling activities.